Genome Mining and Metabolic Profiling Reveal Cytotoxic Cyclodipeptides in Streptomyces hygrospinosus var. Beijingensis - Dashan Zhang; Junbo Wang; Yongjian Qiao; Baixin Lin; Zixin Deng; Lingxin Kong; Delin You (Antibiotics, 2022)
Two new cyclodipeptide (CDP) derivatives (1–2) and another seven known cyclodipeptides (3–9) were isolated from Streptomyces 26D9-414 by the genome mining approach combined with genetic dereplication and the “one strain many compounds” (OSMAC) strategy. The structures of the new CDPs were established on the basis of 1D- and 2D-NMR and comparative electronic circular dichroism (ECD) spectra analysis. The biosynthetic gene clusters (BGCs) for these CDPs were identified through antiSMASH analysis. The relevance between this cdp cluster and the identified nine CDPs was established by genetic interruption manipulation. The newly discovered natural compound 2 displayed comparable cytotoxicity against MDA-MB-231 and SW480 with that of cisplatin, a widely used chemotherapeutic agent for the treatment of various cancers.